Tax-Transfers Schemes, Informality, and Search Frictions in a Small Open Economy - Robayo-Abril, Monica (Washington, DC: World Bank, 2018)
This paper evaluates the impact of market-oriented structural reforms, in particular labor market policies, social assistance programs, and trade liberalization on long run unemployment, wage inequality, and the distribution of employment across sectors in a small open economy with search frictions and idiosyncratic productivity shocks. The paper builds a search and matching model of a labor market with a large informal sector and estimates the model using Colombian household-level data. Changes in labor taxes may have sizable aggregate, compositional, and distributional effects if workers associate high payroll taxes with more valuable and efficient social security services. The higher is the valuation of the services, the higher is the reduction in the log-wage gap. An expansion of public health insurance to informal sector workers has minor aggregate and distributional effects. Changes in relative prices that negatively affect the relative profitability of the formal sector have quite sizable aggregate effects, producing more long-run unemployment and informality, and increasing unemployment duration.